2016
DOI: 10.3233/jad-151175
|View full text |Cite
|
Sign up to set email alerts
|

The Memory Binding Test: Development of Two Alternate Forms into Spanish and Catalan

Abstract: The MBT A and B in Spanish and Catalan showed similar outcomes and can be considered equivalent. Moreover, the thorough methodology presented here for the transcultural adaptation and equivalence study, could serve as a model for future adaptations of the MBT and other verbal tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The neuropsychological assessment took place on average 10.6 months (SD = 5.81) before the MRI session. EM was assessed using the Spanish adapted version of the Memory Binding Test (MBT) (Gramunt et al, 2016), an instrument that was developed for detecting subtle memory impairment in the cognitively intact population (Buschke, 2014). Previous studies have demonstrated the ability of the MBT (formerly referred as Memory Capacity Test [MCT]) to discriminate subjects with cerebral Aβ deposition (Papp et al, 2015), and to successfully predict the incidence of MCI longitudinally (Mowrey et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The neuropsychological assessment took place on average 10.6 months (SD = 5.81) before the MRI session. EM was assessed using the Spanish adapted version of the Memory Binding Test (MBT) (Gramunt et al, 2016), an instrument that was developed for detecting subtle memory impairment in the cognitively intact population (Buschke, 2014). Previous studies have demonstrated the ability of the MBT (formerly referred as Memory Capacity Test [MCT]) to discriminate subjects with cerebral Aβ deposition (Papp et al, 2015), and to successfully predict the incidence of MCI longitudinally (Mowrey et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Free, cued, and paired recall are assessed in immediate and delayed (after 25–35 min) trials. We used the Spanish version of the MBT that we have recently adapted, normed, and validated [34]. The following main variables were gathered and analyzed: immediate total paired recall (TPR), immediate total free recall (TFR), total delayed paired recall (TDPR), and total delayed free recall (TDFR).…”
Section: Methodsmentioning
confidence: 99%
“…Spanish translation and transcultural adaptation of the MBT. Although there is a Spanish version of the MBT for Spain 44 - 46 and another for Colombia, 47 some words are infrequent in Argentina (zumo, laton, taburete, alicates, ensaimada, aspirador, colgantes, vitrina, cipres, among others). These could have affected the Encoding Specificity and Binding, two important aspects of the MBT.…”
Section: Methodsmentioning
confidence: 99%